Effects of corporate hedges on firm exposure and firm value: empirical evidence from US - Huang, Xiaoyi (2017)
In this article, we examine the effect of the use of derivatives for hedging purpose on firm exposure and firm value and sort the investigation by different market risks, consisting of interest rate risk, foreign exchange rate risk and commodity price risk, against a background of the implementation of SFAS 133 in 1998. Focusing on a sample based on the Nasdaq-100 Index between 2007 and 2016, we establish a formula to evaluate firms’ interest rate exposure, foreign exchange rate exposure and commodity price exposure in different fiscal years respectively, refer to previous research. We make regressions to examine the effect of the use of derivatives for hedging purpose on firm exposure and firm value measured by the natural log of Tobin’s Q. We find that the usage of interest rate and foreign exchange derivatives which are designated as hedges has an impact on the reduction of individual firm corresponding exposure and the increase in firm values, whereas the extent of these hedging also has a role to play in adding firm values. As for commodity price exposure, the empirical study’s result indicates that the use of commodity hedging derivatives is negatively correlated to hedge premiums, as well as the extent of commodity hedging. Except for the commodity price, almost all of our findings are in accordance with our assumption and existing research. While the majority of earlier studies fail to achieve significant results, most of the estimated coefficients we gain from the regression are statistically significant based on the accurate data.